Integrated analysis of myeloperoxidase in gastric health and cancer: associations with pepsinogen levels, immune regulation, and prognosis in a large healthy population-based and TCGA cohorts - Zhou, Junteng; Kong, Qihang; Liu, Xiaojing; Huang, Yan (Frontiers in Immunology, 2025)
BackgroundMyeloperoxidase (MPO) is a key enzyme involved in immune responses and oxidative stress, yet its roles in gastric physiology and gastric cancer remain incompletely understood. This study comprises two independent analyses: (1) to investigate the association between MPO and gastric mucosal injury markers (pepsinogen I, II, and PGR) in a large healthy population, and (2) to evaluate the prognostic significance and immune-regulatory mechanisms of MPO in gastric adenocarcinoma (GA).MethodsWe analyzed data from 16,943 individuals in a healthy population-based cohort and 375 GA patients from The Cancer Genome Atlas (TCGA). In the healthy cohort, multivariate linear regression was used to evaluate associations between MPO and pepsinogen levels. In the GA cohort, survival analyses (OS, DSS, PFI) were conducted using Kaplan-Meier and Cox regression models. Gene expression analysis, functional enrichment (GO, KEGG, GSEA), and immune infiltration analysis (ssGSEA) were performed to explore MPO-related mechanisms in GA.ResultsIn the healthy cohort, MPO was inversely associated with PGR (β = -0.009, P < 0.0001) and PGI (β = -0.057, P < 0.0001). Subgroup and threshold effect analyses revealed non-linear associations and stronger effects among hypertensive individuals, smokers, and alcohol consumers. In the TCGA cohort, high MPO expression was an independent predictor of poor OS (HR = 2.781, P = 0.002) and DSS (HR = 3.667, P < 0.001). Functional analyses showed that MPO was associated with immune-related pathways and increased infiltration of macrophages (R = 0.379, P < 0.001) and dendritic cells (R = 0.377, P < 0.001).ConclusionThis study highlights the distinct roles of MPO in gastric mucosal injury and gastric cancer. In healthy individuals, MPO is associated with markers of gastric mucosal damage, while in GA patients, MPO serves as a prognostic biomarker linked to immune dysregulation. These findings suggest that MPO may be a potential target for monitoring or intervention in gastric mucosal injury and gastric cancer.